CONVERSATIONAL GREETINGS IN DIFFERENT CULTURE (Jurnal Mentari, 2012)
Kata sapaan adalah kata-kata yang kita ucapkan apabila kita bertemu dengan seseorang. Setiap negara berbeda cara menyapakan, baik yang disebabkan oleh perbedaan budaya maupun gaya hidup (individualisme dan berkelompok). Apabila kita berkunjung ke negara lain, kita harus mengetahui perbedaan ini agar tidak terjadi kesalahpahaman. Tulisan ini akan mengemukakan perbedaan-perbedaan yang terdapat di berbagai tempat seperti Bukerebe, Yoruba, China, Spanyol, Indonesia dan Aceh dengan negara yang berbahasa Inggris seperti Australia. Tujuan penulisan adalah agar orang-orang mengerti perbedaan yang terjadi sehingga dapat menghindari kesalahpahaman dalam berkomunikasi. Kata Kunci : Kata Sapaan, Budaya   REFERENCES   Akhimien, EP 2004, ‘The use of ‘How are you?’ in Nigerian society’, Journal of Pragmatics, vol. 36, pp. 2055 – 2058, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Akindele, F 1990, ‘A sociolinguistic analysis of Yoruba greetings’, African Languages and Cultures, vol. 3, no. 1, pp. 1 – 14, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Badt, KL 1994, “A world of difference greetings!” Children Press, Chicago. Béal, C 1992, ‘Did you have a good weekend? Or why there is no such thing as a simple question in cross-cultural encounters?’ Australian Review of Applied Linguistics, vol. 15, no. 1, pp. 23 – 52. Golebiowski, Z 2010, ‘Conversational routines’, Topic 8, Intercultural communication, Study Guide, Deakin University. Kezilahabi, E 2001, ‘A phenomenological interpretation of Kerebe greetings’, Journal of African Cultural Studies, vol. 14, no. 2, pp. 181 – 192, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Lee, C.F.K 2004, “Written request in emails sent by adult Chinese Learners of English”, Language Culture and Curriculum, vol. 17, no. 1, pp. 58 – 72, retrieved June 23, 2009, from Taylor & Francis database. Pinto, D 2008, ‘Passing greetings and interactional style: a cross-cultural study of American English and Peninsular Spanish’, Multilingua, vol. 27, pp. 371 – 388, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Schleicher, AF 1997, ‘Using greetings to teach cultural understanding’, The Modern Language Journal, vol. 8, no. 3, pp. 334 – 343, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Song-Cen, C 1991, ‘Social distribution and development of greeting expressions in China’, Int’l. J. Soc. Lang, vol. 92, pp. 55 – 60, retrieved 15 May 2010, Linguistics and Language Behavior Abstracts. Tiono, NI 2002, ‘Language and culture in relation to intercultural communication in a business context’, Puslit Petra, vol. 4, no. 1, retrieved 30 May 2010 <http://puslit2.petra.ac.id/ejournal/ index.php/ing/article/viewfile/15484/15476>.